2021
DOI: 10.15376/biores.17.1.223-242
|View full text |Cite
|
Sign up to set email alerts
|

Heat sealing evaluation and runnability issues of flexible paper materials in a vertical form fill seal packaging machine

Abstract: Vertical form fill seal machines are commonly used to form pouches. This paper aimed to optimize the sealing parameters and evaluate the runnability of flexible paper-based packaging materials with a polyethylene coating, differentiated by their grammages and thicknesses. This was done in comparison with a commercial plastic film, an oriented polypropylene and polyethylene laminate, using two different sealing jaw patterns in an industrial-scale vertical form fill seal machine. Based on the results obtained, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…As observed in thermoplastic materials, paper‐based materials had no major effects on the visual appearance. Merabtene et al 11 has reported that as the paper‐based material reaches its plateau sealing temperature, it would have relatively consistent seal strength throughout the temperature ranges. Figure 5 reveals that Paper 70 + 15 PE sealed at a lower temperature compared with the thicker grammage, Paper 90 + 30 PE.…”
Section: Resultsmentioning
confidence: 99%
“…As observed in thermoplastic materials, paper‐based materials had no major effects on the visual appearance. Merabtene et al 11 has reported that as the paper‐based material reaches its plateau sealing temperature, it would have relatively consistent seal strength throughout the temperature ranges. Figure 5 reveals that Paper 70 + 15 PE sealed at a lower temperature compared with the thicker grammage, Paper 90 + 30 PE.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers suggest that by identifying the importance of crucial packaging elements, the manufacturers in the food industry should adopt a concurrent approach to include marketers, logistics experts, food scientists, and environmental managers in the design and development of packaging in the food supply chain. According to Merabtene et al (2022), food packaging provides food safety, enables marketing, and facilitates ease of transportation. Packaging protects the content from crushing or environmental impacts.…”
Section: Design For Recovery and Recycling (Dfrr)mentioning
confidence: 99%
“…At the beginning of the packaging operation, the package ISSN 2454-5880 29 film is pulled over a forming collar (mold, forming collar, shoulder), and then after all necessary processes (pack forming, package edge cutting and sealing, product filling, package mouth (top) sealing, package transfer, classification) and cartoning) a fully sealed protective package full of product is created. While all the relevant operational stages are very important, the milestones of the packaging process are the development of package sealing systems (Merabtene, et. al.…”
Section: Introductionmentioning
confidence: 99%